Possible hormone predictors of physical performance in adolescent team sport athletes - Martin, A. C.; Heazlewood, I. T.; Kitic, C. M.; Lys, I.; Johnson, L. (The Journal of Strength and Conditioning Research, 2019)
The research aim of this study was to determine possible hormone predictors of physical performance in adolescent team sport athletes. Saliva samples were collected immediately before performance testing sessions from 114 state squad athletes (77 males, 37 females) participating in either Australian football, basketball, hockey, or netball. Participants completed tests of aerobic and anaerobic capacity, agility, power, and speed. Samples were collected over 22 months at quarterly, six-monthly, and/or yearly intervals depending on the testing schedule of the athlete. Saliva was analyzed for testosterone (T), cortisol (C), estradiol (E), and progesterone (P) levels. A strong negative correlation existed between multistage fitness test performance and T:E ratio (r = -0.76, p = 0.01) in females not taking oral contraceptives, and a strong positive correlation existed between repeat agility total time and estradiol levels (r = -0.71, p = 0.001) in females taking oral contraceptives. In males, strong negative correlations were evident for individual changes in planned agility time and estradiol levels (r = 0.87, p = 0.02), and countermovement jump (CMJ) height and T:C (r = -0.88, p = 0.01). In females taking oral contraceptives, a strong positive correlation was noted between individual change in yo-yo intermittent recovery test performance and T:E (r = 0.74, p = 0.01) and a strong negative correlation was noted between 20-m speed and T:P (r = 0.73, p = 0.01). In females not taking oral contraceptives, a strong negative correlation was found between individual change in CMJ height and T:P (r = -0.72, p = 0.02). The findings show that in adolescent team sport athletes, the P:E, T:E, and the T:P ratios are important predictors of performance in tests of physical capacity. The findings also indicate that estradiol and progesterone have a predictive function in the physical performance of adolescent male team sport athletes.